Public Response To Media Relations Strategies Amidst COVID-19 Crisis - Sri Utami Nurhasanah; Sarah Fitriyani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to investigate the public response to media relations strategies amidst the COVID-19 crisis. Employing a purposive sampling method, participants will be selected based on their diverse backgrounds and exposure to media coverage during the pandemic. Data will be collected through semi-structured interviews and analyzed using thematic analysis. The study seeks to uncover insights into how the public perceives and engages with media communication strategies employed during the crisis. Results will shed light on the effectiveness of different communication approaches and provide recommendations for enhancing communication strategies during similar crises in the future.